O jogo pedagógico seixos: Uma análise piagetiana do desenvolvimento do raciocínio lógico-matemático - Rodrigues, Saulo José Ramos (2020)
The main objective of this work is to analyze the pedagogical game of Seixos, as a strategic game, in the process of developing logical-mathematical reasoning in multiplication learning. This was a qualitative research, of the case study type, carried out with elementary school students from a public school of regular time in the state school system of the town of Inhumas, Goiás. The investigation took place during four classes with the game Seixos, which is a board game suitable for learning the operations of addition and multiplication, and in this work, we opted for multiplication. During the development of the proposal, the students plays were filmed, their speeches were recorded and notes were made in a field notebook. During the development of the game, students were observed regarding the questions and the strategies they developed during their plays. Subsequently, all the material was transcribed, which, analyzed in the light of Jean Piaget's theoretical framework, revealed the following categories of analysis: exercise game, symbolic game, game of rules and aspects of the development of logical-mathematical reasoning. In the analyzes, it was noticed, according to Piaget's theory, the presence of intra and inter balances and characteristics of reflecting abstraction, aspects of a possible development of logical-mathematical reasoning.